El agalma de Roma : Roma | Alfonso Cuarón | 2018 - Suárez, Iara (2019)
This article works on the film Roma directed by Alfonso Cuaron (2018), inspired by the director´s childhood and the women who rised him. In this film, a woman from the Mexican aristocracy and her employee face distressing circunstances and invent a knowledge there, without men. Taking this situation as the axis, the work proposes to think about the agglutinating component in contemporary social link, taking the case of feminism as a symptomatic response to the discontents in the civilization, in its difference within the links that come from The-name-of-Father institutions.